Accelerated orthodontic treatment ‐ what's the evidence?. (March 2017) - Miles, P
Abstract: The demand and accessibility of orthodontic care has increased but has also been accompanied by patient requests for shorter treatment times. Longer orthodontic treatment increases the risk of decalcification, gingival recession, and root resorption and so shorter treatment times have multiple advantages as well as appealing to patient's desires. Numerous techniques and materials have been suggested to reduce treatment times but, in most cases, are based upon selected case reports with no prospective clinical trials to validate claims. The present review examines many of the current options purported to accelerate orthodontic tooth movement and the level of evidence presently available. There is some evidence to suggest that low‐level laser therapy and a corticotomy involving the raising of a muco‐periosteal flap are associated with accelerated orthodontic tooth movement; however, the current level of evidence is low to moderate in quality. For this reason, further research is required before routine application could be recommended.